Η μοναξιά στη θεωρία του Winnicott - Γαλανάκη, Ε. (Επετηρίς Φιλοσοφικής Σχολής της Φιλοσοφικής Σχολής του Πανεπιστημίου Αθηνών, 2003)
This study discusses and evaluates the views of Donald W. Winnicott (1896-1971), a distinguished British pediatrician and psychoanalyst, which explicitly or implicitly are related to loneliness and solitude. Α theoretical approach to the developmental origins of loneliness is as yet to be formulated in the field of developmental psychology. Notions such as the capacity to be alone, the good-enough mother, holding and mirroring, true and false self, childhood psychotic isolation, illusion and disillusionment, transitional object and transitional phenomenon, potential space, playing and creative activity, the non-communicating core self, the “journey” from absolute dependence towards independence, etc., are discussed in the light of their implications for the understanding of loneliness and solitude experiences. The exploration and interpretation of these notions show their usefulness in the construction of a developmental model of loneliness and solitude as well as their fruitfulness for further empirical research on this topic.